Preferensi Siswa SMP terhadap Materi Cerita Fantasi: Membaca Cerita atau Menyimak Podcast - Claritas, Ingit Mreta; Ambarwati, Ari (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research was conducted to map students' preferences for reading fantasy story books or listening to fantasy stories on podcasts. This research aims to determine junior high school students' preferences for reading material, whether they choose to read fantasy stories through storybooks or listen to fantasy stories on podcasts. The data sources for this research are questionnaires and interviews, while the data collection techniques are distributing questionnaires via Google Form and interviews with students. Data analysis uses reduction techniques, presenting data and conclusions. The research subjects consisted of three schools, namely 15 students from SMP Tamansiswa Batu, 10 students from MTs Hasyim Asyari Batu and 10 students from SMPN 25 Malang. The results of this research are (1) This preference shows that podcast media can be used more effectively when learning, especially in fantasy stories, and (2) between female and male students, most of them both like podcast media for learning because students can easier to understand than reading a book.